Is Microthrombosis the Main Pathology in Coronavirus Disease 2019 Severity?—A Systematic Review of the Postmortem Pathologic Findings. (20th May 2021) - Fahmy, Omar H.; Daas, Farah M.; Salunkhe, Vidyulata; Petrey, Jessica L.; Cosar, Ediz F.; Ramirez, Julio; Akca, Ozan
Abstract : Objectives: This systematic review attempts to retrieve and report the findings of postmortem studies including the histopathologic data of deceased coronavirus disease 2019 patients and to review the manifestations of coronavirus disease 2019–associated thrombotic pathologies reported in the recent literature. Data Sources: PubMed, Excerpta Medica Database, and Cochrane library between December 1, 2019, and August 26, 2020. Study Selection: Investigators screened 360 unique references, retrieved published autopsy series, and report on the postmortem histopathologic information on patients who had died of coronavirus disease 2019. Data Extraction: Investigators independently abstracted all available data including study design, participant demographics, key histopathologic findings, disease severity markers, duration of hospital stay, and cause of death. Data Synthesis: From the 65 eligible studies, 691 total completed autopsies were included in evidence synthesis. Histopathologic evaluation of the lungs revealed presence of diffuse alveolar damage in 323 of 443 patients and pulmonary microthrombi in 242 of 326 patients. Deep venous thrombosis and pulmonary embolism were found in 41% and 15%, respectively, of the cadavers examined for thromboembolic events. d -dimer levels were generally higher in patients with severe clinical course of coronavirus disease 2019. Plasma levels of ferritin, lactate dehydrogenase, interleukin-6, and C-reactive protein were higher in nonsurvivors when compared with survivors. Overall, microthrombi and extensive angiogenesis of lung vasculature were the most common pathologic findings in the lungs and microthrombi in most of the assessed organ-tissue. Conclusions: Diffuse alveolar damage was the most predominant feature in the lungs of coronavirus disease 2019 patients who underwent postmortem assessment. Widespread pulmonary microthrombosis and extensive pulmonary angiogenesis, in addition to frequent pulmonary and extrapulmonary microthrombotic and thromboembolic findings in patients with coronavirus disease 2019, appear to be consistent with the disease-specific hypercoagulability. Further discovery efforts in assessing the link between coronavirus disease 2019, hypercoagulable state, and immunothrombosis are warranted. In the interim, increased attention to anticoagulant treatment approaches in coronavirus disease 2019 patients is needed.